Identifying key drivers of alcohol use disorder among migrant workers from Myanmar in Thailand: A cross-sectional study - Naw Paw Eh Doh; Roshan Kumar Mahato (International Journal of Public Health Asia Pacific, 2026)
Background: Alcohol consumption is a global public health concern, with rising rates contributing to significant health and social consequences. Studies indicate a high prevalence of drinking behaviour among this population, yet limited research exists on the key factors influencing their alcohol consumption. Objectives: This study aimed to determine the prevalence of alcohol use disorder (AUD) and identify the factors influencing it among Myanmar migrant workers in the Thai-Myanmar border areas of Thailand. Methods: A cross-sectional survey was conducted among 448 Myanmar migrant workers aged 18-59 in three randomly selected districts of Tak Province, Thailand. Participants were chosen using multistage sampling from six subdistricts with high migrant populations. Multivariable logistic regression was used to identify factors associated with AUD, with statistical significance of P < 0.05. Results: Among the 448 respondents, 16.74% had AUD (95% CI: 13.55-20.50) while 83.26% were low-risk drinkers. Multivariable analysis showed higher odds of AUD among Burmese ethnicity (Adjusted Odds Ratio [AOR]: 2.04, 95% CI: 1.14-3.66), those with a monthly family income above 10,000 THB (AOR: 2.38, 95% CI: 1.35-4.19), those living in rented housing (AOR: 3.30, 95% CI: 1.48-7.33), and individuals with a poor scored attitude toward alcohol (considering alcohol consumption is appropriate) (AOR: 3.61, 95% CI: 1.35-9.67). Peer drinking (AOR: 10.84, 95% CI: 3.79-31.04) and easy access to alcohol (AOR: 3.30, 95% CI: 1.36-8.01) were also strongly associated with AUD. Conclusion: This study investigates the prevalence and contributing factors of AUD among migrant workers from Myanmar, underscoring the urgent need for targeted intervention strategies.